2008
DOI: 10.1097/pas.0b013e3180dc92ab
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Nodes After Preoperative Chemoradiotherapy for Rectal Carcinoma: Number, Status, and Impact on Survival

Abstract: The number and status of lymph nodes examined is crucial for tumor staging. Impact of preoperative chemoradiotherapy on lymph nodes status and survival is still controversial in rectal carcinoma. The aim of this study was (i) to define the impact of preoperative chemoradiotherapy on the number of both retrieved and positive lymph nodes in rectal cancer specimen, (ii) to evaluate the influence of the number of lymph nodes retrieved on survival in patients treated by preoperative chemoradiotherapy. From 1994 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
5
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(119 citation statements)
references
References 24 publications
5
106
5
1
Order By: Relevance
“…Many studies (Nagtegaal et al, 2002;Wichmann et al, 2002;Baxter et al, 2005;Sermier et al, 2006;Rullier et al, 2008;Mekenkamp et al, 2009) have reported retrieved from patients with locally advanced rectal cancer who received preoperative chemoradiation, probably depletion (Marks et al, 2010). A study (Bakter et al, 2005) based on the surveillance, Epidemiology and End Result (SEER) registry showed that only 19% of patients with stage III rectal cancer had at least 12 retrieved lymph nodes after preoperative chemoradiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (Nagtegaal et al, 2002;Wichmann et al, 2002;Baxter et al, 2005;Sermier et al, 2006;Rullier et al, 2008;Mekenkamp et al, 2009) have reported retrieved from patients with locally advanced rectal cancer who received preoperative chemoradiation, probably depletion (Marks et al, 2010). A study (Bakter et al, 2005) based on the surveillance, Epidemiology and End Result (SEER) registry showed that only 19% of patients with stage III rectal cancer had at least 12 retrieved lymph nodes after preoperative chemoradiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence the number of lymph nodes retrieved, including tumor (size, stage) (Baxter et al, 2005), and the patient (age, sex) (Thorn et al, 2004;Gao et al, 2013), and neoadjuvant CRT (Rullier et al, 2008;Doll et al, 2009;Wang et al, 2009). Recent studies demonstrated that the total number of retrieved LNs was decreased due to preoperative chemoradiation, probably because of lymph node atrophy, fibrosis and lymphocyte depletion caused by radiotherapy or/and chemotherapy, and the number of harvested LNs was frequently less than12, despite the maintenance of vigorous surgical standards (Rullier et al, 2008;Doll et al, 2009;Wang et al, 2009;Lee et al, 2012). Lee et al (2012) found that <12 LNs were harvested in 30.5% patients after preoperative CRT.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found that, LNR is not only an important prognostic indicator, but also a more accurate stratification system than the current metastatic lymph node number-based staging system in colorectal cancer (Peschaud et al, 2008;Rosenberg et al, 2008;Kim et al, 2009;Moug et al, 2009). Preoperative chemoradiotherapy (CRT) followed by total mesorectal excision (TME) is the current standard of care for patients with T3 or T4 tumors and/or positive lymph nodes (Kapiteijn et al, 2001;Sauer et al, 2004). However, some studies have demonstrated that the number of harvested LNs is significantly decreased in rectal cancer patients received preoperative CRT (Rullier et al, 2008;Doll et al, 2009;Wang et al, 2009). The number of harvested LNs in rectal cancer patients treated with preoperative CRT is frequently fewer than 12, as recommend by the American Joint Committee on Cancer (AJCC) and the National Cancer Institute (Goldstein et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative CRT leads to a significantly reduced number of LN for examination in the tumor specimen [30][31][32][33][34]. It is associated with lymphocyte depletion in the LN and with tissue fibrosis, which makes the LN smaller and more difficult to be identified.…”
Section: Discussionmentioning
confidence: 99%